Genetic correlations between performance at different racing distances in Thoroughbreds - da Mota, Marcilio Dias Silveira (Elsevier, 2006)
The aim of the present study was to estimate genetic correlations between time at different racing distances in Thoroughbred racehorses based on data provided by Turftotal Ltda. The traits evaluated were times in seconds for distances of 1000, 1100, 1200, 1300, 1400, 1500 and 1600 m, with a total of 32,145 races and 238,890 time records being analyzed. The (co)variance components necessary to obtain the genetic correlations were estimated using the MTGSAM program in a two-trait animal model. The model used for analysis of the data involved animal and permanent environmental random effects, and race, sex, age and post position at start as fixed effects. All genetic correlations were positive and ranged from medium (0.54) to high (0.93). © 2006 Elsevier B.V. All rights reserved.
Keywords: Distance performance; Genetic parameters; Thoroughbred